Knowledge, attitude and practice of elderly individuals towards successful aging at Klinik Pakar Perubatan, Hospital Universiti Sains Malaysia, Kelantan - Ida Seriwati, Ismail (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
This research aims to determine the level of knowledge, attitude and practice of elderly towards successful aging. Samples were recruited by purposive sampling among elderly, aged 60 years and above, at the Klinik Pakar Perubatan Hospital Universiti Sains Malaysia (n=1 00). A constructed questionnaire was used to collect the data. The mean age of samples was 66 years. The majority of the respondents scored highly in knowledge (68%), had a positive attitude (n=74), and good level of practice (53%} towards successful aging. The status of successful aging was moderate (n=53}. Spearman Correlation Coefficient test revealed significant positive correlations between knowledge and attitude (r-0.421, P<0.01 ), and practice and successful aging (r-0.569, P<0.01). However, no significant correlation was found between attitude and practice. In conclusion, the present findings revealed that practice was significantly related to higher successful aging status. Therefore, healthy lifestyle practices, such as continuous participation in appropriate physical activity and eating healthy nutritionous diet, should be encouraged to optimize successful aging in the late years of life. Keywords: successful aging, knowledge, attitude, practice.